(untitled) ("Journal "U". Economy. Management. Finance.", 2018)
The article describes the problem of "serial depositors" from the point of view of the banking system. The concept of "serial depositors" is disclosed. There are some main reasons for the existence of such a situation in modern Russia in the article. The activities of the Deposit Insurance Agency are described, unfortunately, the current deposit insurance system does not generate the cleanest incentives for depositors and for the not-so-big banks.